Metoda Multi Soil Layering Dalam Pengolahan Air Gambut Dengan Variasi Hydraulic Loading Rate Dan Material Organik Pada Lapisan Anaerob - Tiara Adinda; Shinta Elystia; Edward HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Peat water has characteristics which are: maroon, content high organic matter and the iron also high enough, the taste is sour with pH 3-5, and low hardness (Idaman, 1999). Generally, people who live in areas such as Kabupaten Kampar are difficult to obtain clean water because only water from the river that exist which is peat water, so they use the rain water for daily needs, even though some of them use Mineral Water (Branded Water Gallon ) with the expensive price. During the dry season, people forced to use the peat water for daily needs such as cooking, washing, and toilet. If it is done continuously, it will cause disruption to health such as skin diseases, diarrhea, and others. In this research, an attempt has been made to peat water change into clean water using Multi-Soil-Layering method (MSL). The variable in this research is an organic material in an anaerobic layer which is an active banana peel charcoal and active coconut shell charcoal. This research aims to determine the efficiency of removal parameters pollutant, such as: pH, turbidity, and Mn on peat with MSL method, to study the influence of variation of organic material in the soil mixture in the anaerobic layers and variations of Hydraulic Loading Rate (HLR) to the efficiency water treatment peat with MSL method, and compare the results with PERMENKES No.416 of 1990 about Monitoring Terms and Water Quality and Regulation No. 82 of 2001 on Water Quality Management and Water Pollution Control. Optimal results which is obtained in the HLR 500l/m2days are pH from 6.51 to 6.82, Mn Metals, and turbidity decreased from 1.277mg/l, 44.56 NTU into 0.500mg/l, and 3.18NTU.Keywords:WaterPeat, MultiSoilLayering, Hydroulic Loading Rate, Variation Organic Material